Analysis of the epidemiological profile of exogenous drug intoxications in the state of Piauí - Brazil, from 2007 to 2019 (Research, Society and Development, 2021)
The estensive variety of drugs, the lack of knowledge of their properties and their overuse can cause damage to to the patient's health, including deaths, representing a challenge for health services. This study had as objective to retrospectively analyze the epidemiological profile of notifications of acute drug poisoning that occurred in Piauí, in the period from 2007 to 2019. This is an epidemiological, descriptive, quantitative study, analyzing the epidemiological profile of drug poisonings reported in Piauí, from 2007 to 2019. In Piauí, 6,210 cases were reported during the period analyzed, revealing 2019 was the year with the highest number of drug poisonings in absolute values (17,74%). Regarding the number of notifications in the urban area (n=5,189) where the female gender is predominant (n=4,433), prevailing the age groups of 20-39 years (n=2,510) and 15-19 years (n=1,012). The suicide attempt was responsible for 3,450 cases. This study aims to contribute to the improvement of public health policies with a focus on prevention, guidance and the adoption of measures to minimize this situation, with special attention to young adults and women who are the main responsible for notifications of drug poisoning in Piauí.